Problematika Penerapan Asesmen Berbasis HOTS (Higher Order Thinking Skills) di Sekolah Dasar - Ningsi, Ayu; Shaleh, Shaleh (Universitas Indraprasta PGRI Jakarta, 2024)
This article describes the obstacles of teachers and students at the elementary school level in implementing higher-order thinking skills (HOTS) based assessments. This research will illustrate the problems faced by teachers and students, especially in elementary schools, in implementing assessments based on higher-order thinking skills (HOTS). This research is a literature study, using data obtained from research that has been published in national and international journals that are available online. Researchers search for research articles using search engines such as Scopus and Scholar. The results of the research show several main points, namely: the lack of teachers' ability to develop assessment instruments based on higher-order thinking skills (HOTS), deduction abilities, error analysis, perspective analysis, decision-making, experience, as well as problem-solving and discovery abilities of students' thinking abilities, some large is still at a low level. In dealing with these obstacles by providing training to teachers regarding the preparation of HOTS-based assessment instruments, adapting measurements to students' learning styles to reveal how HOTS ability levels can be linked to their learning style preferences, as well as by utilizing educational technology to support the process of developing assessment instruments Higher Order Thinking Skills (HOTS).